Predictive factors for pneumonia development and progression to respiratory failure in MERS-CoV infected patients. Issue 5 (November 2016) - Ko, Jae-Hoon; Park, Ga Eun; Lee, Ji Yeon; Lee, Ji Yong; Cho, Sun Young; Ha, Young Eun; Kang, Cheol-In; Kang, Ji-Man; Kim, Yae-Jean; Huh, Hee Jae; Ki, Chang-Seok; Jeong, Byeong-Ho; et al.
Summary: Background: After the 2015 Middle East respiratory syndrome (MERS) outbreak in Korea, prediction of pneumonia development and progression to respiratory failure was emphasized in control of MERS outbreak. Methods: MERS-CoV infected patients who were managed in a tertiary care center during the 2015 Korean MERS outbreak were reviewed. To analyze predictive factors for pneumonia development and progression to respiratory failure, we evaluated clinical variables measured within three days from symptom onset. Results: A total of 45 patients were included in the study: 13 patients (28.9%) did not develop pneumonia, 19 developed pneumonia without respiratory failure (42.2%), and 13 progressed to respiratory failures (28.9%). The identified predictive factors for pneumonia development included age ≥45 years, fever ≥37.5 °C, thrombocytopenia, lymphopenia, CRP ≥ 2 mg/dL, and a threshold cycle value of PCR less than 28.5. For respiratory failure, the indicators included male, hypertension, low albumin concentration, thrombocytopenia, lymphopenia, and CRP ≥ 4 mg/dL (all P < 0.05). With ≥ two predictive factors for pneumonia development, 100% of patients developed pneumonia. Patients lacking the predictive factors did not progress to respiratory failure. Conclusion: For successful control of MERS outbreak, MERS-CoV infected patients with ≥ two predictive factors should be intensively managed from the initial presentation. Highlights: Predictive factors for pneumonia progression in MERS patients were investigated. Clinical variables measured within three days from symptom onset were used. Six predictive factors for pneumonia development and respiratory failure were found. With ≥ two predictive factors for pneumonia, 100% of patients developed pneumonia. Patients lacking the predictive factors did not progress to respiratory failure.